Dynamics of Change and Development in Islamic Education-al Organizations from the Perspective of Visionary Leadership (International Journal of Education and Literature, 2025)
This study explores the dynamics of organizational change and development in Islamic education from the perspective of visionary leadership, focusing on how vision and innovation serve as the driving forces of institutional transformation. The research object is an Islamic educational institution at the secondary level that seeks to adapt to modernization and quality improvement based on Islamic values. The main problem addressed in this study is the weak internalization of vision within organizational culture and the limited integration between spiritual and managerial aspects of leadership. The purpose of this study is to analyze the role of visionary leadership in directing organizational change and fostering adaptive, innovative, and value-driven development within Islamic education institutions. This research employs a qualitative descriptive method, using interviews, observations, and documentation as data collection techniques, analyzed thematically through the Miles and Huberman model. The findings reveal that visionary leadership builds a strategic direction grounded in Islamic values, promotes collective participation, and cultivates a culture of continuous innovation. The synthesis of results indicates that visionary leadership serves as the foundation for effective organizational transformation, harmonizing spirituality and innovation to create an excellent and value-oriented educational institution. In conclusion, strengthening leadership vision is essential to ensure the sustainability and relevance of Islamic education in the modern era.